Implementasi Trilogi Kepemimpinan (Ki Hadjar Dewantara) Di Madrasah Tsanawiyah - Wenny Wijayanti (Media Manajemen Pendidikan, 2019)
The purpose of this study is to: (1) Determine the Implementation of Ki Hajar Dewantara's leadership trilogy in Madrasah Tsanawiyah Al Iman Bulus Purworejo in 2018. (2) Knowing the factors that influence the implementation of the Ki Hajar Dewantara leadership trilogy. (3) Knowing the results of the Ki Hajar Dewantara leadership trilogy implementation. This type of research is qualitative research and is carried out in Madrasah Tsanawiyah Al Iman Bulus Purworejo. Data collection methods are done by interview, documentation and observation. Data analysis uses descriptive qualitative analysis. The results of this study indicate: 1) The implementation of Ki Hajar Dewantara's leadership trilogy in Tsanawiyah Al Iman Bulus Madrasa Purworejo in 2018 has been in accordance with Ki Hadjar Dewantara's leadership principles, namely Ing Ngarso Sung Tulodo, Ing Madyo Mangun Karso and Tut Wuri Handayani. The implementation of the leadership trilogy is reflected in the principal who routinely carries out teachers in teacher meetings that are held for a month of the school, as well as school principals and teachers who have implemented and provided direct examples to students. 2) Factors that support the implementation of the leadership trilogy include: the existence of supporting school facilities and infrastructure, the development of expertise in the field of information technology, the existence of pesantren activities that develop students' character and approach with teachers as a family. 3) The results of the implementation of Ing Ngarso Sung Tuladha in the good category with a score of 94.3%. The results of the implementation of Ing Madya Mangun Karsa were in the good category with a score of 78.7%. The results of the implementation of Tut Wuri Handayani are in the good category with a score of 85%.